Penerapan Metode Debat Aktif Guru Pendidikan Agama Islam (PAI) di SMA Al-Fattah Singosari Malang - Afidah, Maisatul Afidah; Chotimah, Chusnul (Universitas KH. A. Wahab Hasbullah, 2022)
Learning models, learning methods, and strategies in carrying out learning to be effective and efficient are important things in the success of learning that has been designed before implementing LTA (Learning and Teaching Activities). The aim of this research is; (1) Strategies or efforts of PAI teachers in teaching and learning situations using the Active Debate Method; (2) Strengths and weaknesses in applying teaching and learning situations with the Active Debate method at Al-Fattah Singosari High School Malang. The research method in this paper is a qualitative approach and compares the results of the literature collected by the author with the results of observations and interviews that have been carried out by the author at Al-Fattah High School. The results of the analysis by researchers are as follows: (1) Efforts made by teachers of Islamic Religious Education subjects in implementing active debate learning methods at Al-Fattah Singosari High School Malang are by making preparations by means of teachers choosing PAI themes which are used as problem-based learning that became the main theme of the active debate. (2) The advantages and disadvantages found during the implementation of the active debate method in grade 11 Social Studies at SMA Al-Fattah Singosari Malang are as follows, in terms of the advantages of this method being able to make students as capable individuals. While the drawbacks are students who are insecure or lack confidence in what they already know.